Adjusting protein in cattle rations during cold weather - D.R. Ames (Kansas Agricultural Experiment Station Research Reports, 1976)
Two winter trials have indicated that protein can be removed from growing rations during cold weather without lowering average daily gain. Cattle consumed 0.29 and 0.33 lb/hd/da (0.11 and 0.15 kg/hd/da) less protein supplement (soybean oil meal) during winters 1975 and 1976, respectively.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Protein; Rations